Effect of basal and foliar application of boron and zinc on yield attributes in Solanum melongena L. - Chauhan, S. V. S.; Rana, A.; Chauhan, S. (International Journal of Horticultural Science, 2004)
Field experiments were conducted during 1999-2000 and 2000-2001 to study the effect of basal application (BA) of zinc sulphate (5 and 10 mg kg-i soil) or boric acid (1 and 2 mg kg-1 soil) alone or foliar applications (FA) of water or 1% ZnSO4 or 1% H3 B03 or the combinations of both BA and FA of either ZnSO4 or H3 B03 on yield attributes (number of flowers and fruits/ plant, fruit weight, size and total yield). On the basis of the two-year data, it was found that all the treatments of BA as well as FA enhanced yield attributes but the combination of BA of 10 mg kg–1 soil ZnSO4 and FA of 1% H3 B03 gave highest yield as compared to other treatments and control plants.